2009
DOI: 10.1007/s00210-009-0416-x
|View full text |Cite
|
Sign up to set email alerts
|

Topical antiseptics for the treatment of sore throat block voltage-gated neuronal sodium channels in a local anaesthetic-like manner

Abstract: Lozenges for the treatment of sore throat provide relief of discomfort in cases of oral inflammation. This effect has not been fully explained so far. Here, we have examined the proposition that key components of pharmaceutical preparations for the treatment of sore throat which are routinely regarded antiseptics might have sodium channel-blocking, i.e. local anaesthetic-like effects. We investigated the effects of hexylresorcinol, amylmetacresol and dichloro-benzylalcohol on voltage-operated neuronal (Na(V)1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 32 publications
0
22
0
3
Order By: Relevance
“…now, it is also the ingredient of oral anti-septics. oral intake of 4-Hr can prevent some types of tumor occurrence in experimental animals (13). the mechanism of tumor inhibition by 4-Hr is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…now, it is also the ingredient of oral anti-septics. oral intake of 4-Hr can prevent some types of tumor occurrence in experimental animals (13). the mechanism of tumor inhibition by 4-Hr is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A randomised controlled trial on 310 patients showed a significant analgesic effect and improvements in functional impairment scores by use of these pastilles (Wade et al 2011;McNally et al 2010). Recent studies from our group have led to the theory that such pain relief was not merely as a result of an antiseptic action-a possible blocking effect of voltage-gated sodium channels was considered to be a contributing factor and a viable mechanistic pathway (Buchholz et al 2009). …”
mentioning
confidence: 99%
“…В зарубежных исследованиях наиболее изучен терапевтический эффект препаратов, содержащих комбинацию амилметакрезола и дихлорбензило-вого спирта. Опубликованы результаты исследова-ний, подтверждающие высокий анальгезирующий эффект указанного сочетания, подобный действию местных анестетиков [12][13][14][15]. Так, по данным немецких ученых, гексилрезорцин и амилметакре-зол блокировали натриевые каналы в 10-20 раз сильнее, чем лидокаин [13].…”
unclassified
“…Опубликованы результаты исследова-ний, подтверждающие высокий анальгезирующий эффект указанного сочетания, подобный действию местных анестетиков [12][13][14][15]. Так, по данным немецких ученых, гексилрезорцин и амилметакре-зол блокировали натриевые каналы в 10-20 раз сильнее, чем лидокаин [13]. По другим данным, выраженный обезболивающий эффект амилмета-крезола/дихлорбензилового спирта наблюдали уже через 5 мин после применения, и он продолжался в течение 2 ч [14].…”
unclassified
See 1 more Smart Citation